Hemosuccus pancreaticus as a complication of acute necrotizing pancreatitis: A case report - Eduardo Segovia-Vergara; Arturo Alonso; Fernando Torres; Paula De la Rosa Acuña; Rodrigo Mansilla-Vivar (International Journal of Gastrointestinal Intervention)
Hemosuccus pancreaticus (HP) is characterized by hemorrhage from the pancreatic duct through the major duodenal papilla. It represents the least common cause of upper gastrointestinal bleeding (UGIB), occurring in approximately 1 in 1,500 cases and predominantly affecting men. A 58-year-old woman with a history of recurrent pancreatitis presented with severe epigastric pain, vomiting, and diarrhea. Laboratory tests revealed hyperamylasemia. Imaging indicated acute necrohemorrhagic pancreatitis with peripancreatic fluid collections. Despite interventions including drainage and antibiotic therapy, she developed massive hematemesis and hemodynamic instability. Computed tomography indicated active bleeding in the peripancreatic region, and angiography confirmed a diagnosis of HP. Embolization of the gastroduodenal artery was performed; however, the patient died of multiorgan failure. HP, although rare, should be considered in patients with chronic pancreatitis and intermittent UGIB. Diagnosing HP can be challenging, requiring collaboration between gastroenterologists and interventional radiologists. Early intervention is crucial due to the high mortality rate associated with severe cases.